Aqueous Electrodeposition of SmCo Alloys: II. Direct Current Studies - Jei C. Wei; Morton Schwartz; Ken Nobe; Nosang V. Myung (Frontiers in Chemistry, 2021)
Previously, we reported the aqueous electrodeposition of rare earth - iron group alloys. A key factor was the complexation of the metal ions with various coordination compounds (e.g., aminoacetic acids), without which only the ferrous metal and rare earth hydroxides/oxides are deposited. In this work, samarium cobalt (SmCo) alloys were synthesized using direct current (DC) aqueous electrodeposition. The basic electrolyte solution consisted of 1 M samarium sulfamate, 0.05 M cobalt sulfate, and 0.15 M glycine, resulting in deposits containing >30 at% Sm at 60°C with current density of 500 mA/cm2. Supporting electrolytes (i.e., ammonium salts) decreased the Sm content in the deposit. Crystallinity of deposited films altered from nanocrystalline to amorphous as the Sm content increased. Deposits with high Sm content (32 at%) became isotropic with reduction in magnetic saturation (Ms) and coercivity (Hc). A deposition mechanism involving stepwise reduction of the complexed Sm-Co ions by depositing hydrogen atoms was proposed.